Protocol for a systematic review and meta-analysis of the combination of ezetimibe and statins for hyperlipidemia. - Tianfu Yang; Weijuan Li; Weiwei Chen; Donghong Zhu; Yuxi Ren; Xiongfeng Huang (PLoS ONE)
Introduction Hyperlipidemia is increasingly recognized as a significant global health issue, often associated with conditions such as hypertension, diabetes, and obesity. While statins are frequently prescribed to manage lipid levels, recent studies indicate that reliance solely on statin therapy may present certain disadvantages, including prolonged treatment durations, the potential for drug resistance, and various adverse effects. Research indicates that the combination of ezetimibe and statins demonstrates a favorable therapeutic effect in the management of hyperlipidemia. However, existing studies have not consistently confirmed these benefits, and there is no current meta-analysis available. As a result, we will perform a meta-analysis to assess the effectiveness and safety of the combination of ezetimibe and statins in managing hyperlipidemia, aiming to offer evidence-based medical guidance for clinical practice. Methods and analysis The systematic review and meta-analysis will adhere to the PRISMA guidelines for systematic reviews and meta-analyses. We will search for randomized controlled trials that investigate the efficacy and safety of the combination of ezetimibe and statins in treating hyperlipidemia, based on specific criteria. The following electronic databases will be searched by two researchers for relevant records published up to October 1, 2024: Cochrane Central Register of Controlled Trials (CENTRAL) in Cochrane Library, Embase.com, Web of Science, MEDLINE (via PubMed), Wanfang China Database, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM) and Chinese Scientific Journal Database (VIP). They will also check references and relevant journals manually. Two independent reviewers will handle screening, data extraction, and quality assessment. Subgroup analysis, sensitivity analysis, and publication bias analysis will be performed to assess consistency and reliability. Review Manager 5.4 will be used for data analysis and synthesis, while the GRADE approach will be employed to evaluate the overall study's evidence quality. Expected results The findings of this systematic review will be shared with various stakeholders who are interested in the combination of ezetimibe and statins for hyperlipidemia. This will offer valuable insights for researchers undertaking future investigations and for clinical practitioners specializing in the treatment of hyperlipidemia. Ethics and dissemination This study is based on a secondary analysis of the literature, so ethical review approval is not required. The final report will be published in a peer-reviewed journal. Study registration The protocol of the systematic review has been registered on Open Science Framework, with a registration DOI https://doi.org/10.17605/OSF.IO/TEVUY.